Assesment of mineral contents in aerial parts of schizachyrium microstachyum - Villafañe, Roxana Noelia (2013)
Assesment of Mineral Contents in Aerial Parts of Schizachyrium Microstachyum?; Villafañe R., Bernardis A., Gaiad J., Marchevsky E., Pellerano R.; XXXI Reunión Anual Sociedad Biologia de Cuyo, Noviembre 2013, Mendoza. This work describes the determination and evaluation of the mineral composition (Ca, Mg, Fe, Mn and Zn) of aerial parts of Schizachyrium microstachyum grown in two soil series within the Corrientes province, Argentina. This species is part of natural grassland used for extensively livestock production. The sampling process was performed during the summer and winter. Organic matter was eliminated by using dry-ashing digestion. Analyses were performed by inductively coupled plasma optical emission spectrometry (ICP-OES). Principal component analysis (PCA) and hierarchical cluster analysis (HCA) revealed different mineral compositions of the samples collected from the different kind of soils. Samples collected in the Chavarria´s series showed higher concentrations of micronutrients (Fe, Mn and Zn) and macronutrients (Ca and Mg). The average contents of samples collected from Chavarria and Pampin series were: calcium 750 and 735 μg g-1; magnesium 217 and 186 μg g-1; iron 38.1 and 44.3 μg g-1; zinc 13.3 and 12.9 μg g-1; and manganese 110.8 and 84.0 μg g-1, respectively. Mean forage mineral concentrations were compared with beef cattle requirements using a two-tailed t test. Forages from native pastures may meet most but not all mineral requirements of beef cattle, and supplementation of specific minerals, particularly Mg and Fe, may be necessary.